Development and validation of the Self‐Gifting Consumer Behaviour scale. Issue 3 (8th March 2015) - Mortimer, Gary; Bougoure, Ursula Sigrid; Fazal‐E‐Hasan, Syed
Abstract Self‐gifting consumer behaviour (SGCB) is on the rise as consumers seek reward and therapeutic benefits from their shopping experiences. SGCB is defined as personally symbolic, self‐communication through special indulgences, which tend to be premeditated and highly context bound. Prior research into the measurement of this growing behavioural phenomenon has been fragmented because of differences in conceptualisation. This research builds upon the prior literature and through a series of qualitative and quantitative studies, develops a valid, multidimensional measure of SGCB that will be useful for future quantitative inquiry into self‐gifting consumption. Copyright © 2015 John Wiley & Sons, Ltd.